(untitled) (Research, Society and Development, 2021)
The knowledge of the rate of water infiltration in the soil is of fundamental importance for the proper use and management of the soil, in addition to helping in the planning of irrigation and drainage techniques. Mathematical modeling is indicated as a tool capable of anticipating events and pointing out alternatives that lead to the productive maintenance of the environment, and given the difficulty of obtaining water infiltration data in the field, a quick way to obtain data is through the use of simulated rain that provides simulations in conditions that cannot always be represented in the field. Thus, this work aims to simulate, under laboratory conditions, the effect of precipitation, slope and amount of straw on the soil, on the rate of water infiltration into the soil by means of a rainfall simulator and to develop a prediction model of infiltration. Data were statistically analyzed using Multiple Regression and, with the help of the R Studio software, the model was formulated that described the relationship of these variables with water infiltration into the soil. The amount of straw had a greater influence on the infiltration rate, compared to the other factors analyzed, while precipitation had less influence. So that if the amount of straw is guaranteed, even with high rainfall intensities, the infiltration of water into the soil will occur satisfactorily, if the structural conditions of the soil allow it. The adjusted model was of good quality, with all significant coefficients at 5%.